2020
DOI: 10.2478/eces-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oxidation of Polycyclic Aromatic Hydrocarbons in Water By Ferrates(VI)

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are a common part of the environment where they come from burning fossil fuels (through an incomplete combustion process). From a toxicological point of view, PAHs are considered to be carcinogens with a mutagenic and teratogenic effect. On the other hand, ferrates are generally believed to be the ideal chemical agent for water treatment due to their strong oxidation potential. Herein, the efficiency of degradation of PAHs (with the special emphasis on B[a]P) by ferrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…The study showed that ferrates can degrade PAHs, but the resistance to this degradation increases with their molecular weight. In fact, PAHs with two or three benzene rings were totally degraded within 30 min, while those with five or more rings were only partially degraded [ 53 ]. Concerning this method, the main disadvantage is the use of chemicals [ 52 ].…”
Section: Conventional Methods Of Water Treatmentmentioning
confidence: 99%
“…The study showed that ferrates can degrade PAHs, but the resistance to this degradation increases with their molecular weight. In fact, PAHs with two or three benzene rings were totally degraded within 30 min, while those with five or more rings were only partially degraded [ 53 ]. Concerning this method, the main disadvantage is the use of chemicals [ 52 ].…”
Section: Conventional Methods Of Water Treatmentmentioning
confidence: 99%
“…They are most often used as solvents or components in technological processes. Alcohols are also a substance in which potassium ferrate, insoluble in ordinary solvents, may be suspended [1]. In everyday life, above all, we find alcohols containing a single hydroxyl group, the so-called monohydric alcohols, whose general formula can be written as C n H 2n+1 OH.…”
Section: Introductionmentioning
confidence: 99%
“…Various forms of oxidising agent are used for ISCO including hydrogen peroxide (H 2 O 2 ), ozone (O 3 ), percarbonate, permanganate, and persulphate (Devi et al 2016;Watts and Teel 2006;Apul et al 2016) and emerging agents such as ferrates(VI) (Antošová et al 2020). Oxidising agents are typically used in combination with one or more activator (Do et al 2013;Wacławek et al 2017).…”
Section: Introductionmentioning
confidence: 99%